2004
DOI: 10.1023/b:pham.0000022413.43212.cf
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Properties of Various Natural Chemopreventive Agents on the Activation of NF-κB Signaling Pathway

Abstract: These results suggest that natural chemopreventive agents have differential biological functions on the signal transduction pathways in the colon and/or colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
147
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 258 publications
(161 citation statements)
references
References 43 publications
12
147
0
2
Order By: Relevance
“…that SFN did not block IB/ degradation or nuclear import of the NF-B subunits p50 (NF-B1) and p65 (RelA), but could directly interfere with NF-B DNA binding in vitro [41]. By contrast, others have shown that ITCs reduce phosphorylation and increase expression of IB [42][43][44]46]. SFN and PEITC inhibited IKK-mediated phosphorylation of IB in an in vitro assay, suggesting that IKK may be a direct target for modulation by ITCs [44].…”
Section: Hif-independent Control Of Angiogenesismentioning
confidence: 92%
“…that SFN did not block IB/ degradation or nuclear import of the NF-B subunits p50 (NF-B1) and p65 (RelA), but could directly interfere with NF-B DNA binding in vitro [41]. By contrast, others have shown that ITCs reduce phosphorylation and increase expression of IB [42][43][44]46]. SFN and PEITC inhibited IKK-mediated phosphorylation of IB in an in vitro assay, suggesting that IKK may be a direct target for modulation by ITCs [44].…”
Section: Hif-independent Control Of Angiogenesismentioning
confidence: 92%
“…The most common nuclear factor kappa B (NF-kB) is a heterodimer composed of p65 and p50 (Greten and Karin, 2004;Suh and Rabson, 2004). NF-kB is activated by a wide variety of stimuli such as tumor necrosis factor (TNF)-alpha, interleukin-1 (IL-1), LPS, UV light, and oxidative stress (Jeong et al, 2004;Takada et al, 2004b). In most cell types, NF-kB is present in the cytosol in an inactive form and is associated with its inhibitor proteins, called inhibitor of NF-kB (IkBs).…”
Section: Introductionmentioning
confidence: 99%
“…The major mechanism of sulforaphane action was inhibition of nuclear factor-nB (NF-nB) binding to DNA presumably through modulation of intracellular redox conditions via dithiocarbamoylation of essential thiol groups involved in the activation of NF-nB. Sulforaphane-mediated inhibition of LPS-induced NF-nB-mediated transactivation was recently confirmed in HT-29 cells stably transfected with NF-nB luciferase constructs (16). (d) In addition, sulforaphane possesses antiproliferative and apoptosis-inducing properties as shown in various cancer cell lines and in vivo (17,18).…”
Section: Introductionmentioning
confidence: 99%